THE ESSENCE AND OBJECTIVES OF THE DIGITALIZATION OF GOVERNMENT AND PUBLIC SERVICES (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
This article examines the process of digitalizing government and public services, discussing its underlying rationale, key objectives, and current global trends. The authors emphasize that applying digital technologies can enhance the efficiency of government services, save resources, increase transparency, and improve citizen satisfaction. They also highlight how digitization of public services can expand service delivery capabilities, especially in areas such as online education and telemedicine. Drawing on international rankings and statistics, the authors compare Azerbaijan’s existing digitization indicators with those of countries like Turkey, Armenia, and Georgia, underlining both development prospects and the challenges that need to be addressed.Keywords: Digitalization, government services, public services, digital technologies, electronic government, automation, efficiency, transparency, satisfaction, online platforms, accountability, resource saving, innovation, online education.